Polychaetous annelids in the deep Nordic Seas: Strong bathymetric gradients, low diversity and underdeveloped taxonomy. (March 2017) - Oug, Eivind; Bakken, Torkild; Kongsrud, Jon Anders; Alvestad, Tom
Abstract: Not much is known on polychaete diversity in the deep Nordic Seas. Based on data from extensive sampling over three decades, new data on polychaetes covering depths from 550 m to 3800 m are presently reported. On a depth gradient, the number of polychaete families gradually declined from 35 at the upper slope (500–750 m) to 11 at 3800 m. Species diversity in eight polychaete families subjected to critical taxonomic studies showed a gradual decrease from a diverse group of slope species in the upper and middle slope (500–1000 m) to a species poor fauna in the deepest areas (>3000 m), with a distinct break at about 2000 m. Faunal changes were documented both at alpha (sample species richness) and gamma (large area species richness) scales, whereas the break at about 2000 m was clearly from beta (turnover) species richness. Only six species (12%) in the examined families were found in the deepest areas. The slope and deep-water polychaete fauna differs substantially from west Norwegian shelf and costal fauna. Not more than 30% of the species in the examined families were recorded in coastal and shelf waters, and several presumably refer to species complexes. The strong faunal change coincides with the upper border of cold sub-zero temperature deep water at the shelf break and upper slope. Polychaete taxonomy of the deep-water fauna is generally underdeveloped, illustrated by a high proportion of recently described or undescribed species (about 40%) in the examined families. Based on the present results, we hypothesise that the cold Nordic Sea deep-water polychaete fauna differs significantly from the North Atlantic deep fauna and rather is more similar to the fauna of deep Arctic waters.